Eunice orensanzi n.sp. from the western coast of Baja California Sur, México and key to the Mexican Eunice (Polychaeta: Eunicidae) - de León-González, Jesús Angel (Universidad de Costa Rica, 1990)
Eunice orensanzi n.sp., is described based on 20 specimelis collected along me westem coast of Baja California Sur, México, during three oceanographic cruises. Branchiae possess numerous filaments, along a short portion of the body, and has composite bidentate falcigers with a blunt hood. E. orensanzi is closely related 10 E. semisegregala, but differs in several morphological characters, including the number of branchial filaments, the start of me subacicular hooks, and the maxilary formula. A key for the 29 species of Eunice reported for Mexican waters is includedo